Bangtan Sonyeondan (BTS) as Global Phenomenon and Their Impacts on Army’s Social Movements in Indonesia - Retno Ramadhina; Priyoto Priyoto; Liana Chandra Pertiwi (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This research aims to find out the factors behind the success of Bangtan Sonyeondan (BTS) as global phenomenon and the impacts they create on many social movements done by their fans called ARMY (Adorable Representative MC for Youth) in Indonesia. Many researches had been done dealing with the topic but less talked about the social movements done by Indonesian ARMY. The purpose of this study is to analyze the reason why BTS is loved by people of the universe and kinds of social movements done by Indonesian ARMY dedicated to the members. The writers used questionnaires as the instrument to collect the data and qualitative merthod to analyze it. Through analysis, the main reason of BTS, was identified as having a positive group boyband personality, smart and creative, having a sense of empathy, having an independent attitude, never giving up, loving family, and having a strong determination in life. The commitment of BTS ARMY’s causes positive impact similarly from their favorite idol.